AIAA SCITECH 2023 Forum 2023
DOI: 10.2514/6.2023-2030
|View full text |Cite
|
Sign up to set email alerts
|

Damage Detection of CNT/CNC-reinforced Foam-cored Sandwich Composites by Acoustic Emission Tests under Flexural Load

Abstract: Sandwich composites stand out especially in the aerospace industry owing to their high strength-to-weight ratio, one of the most prominent factors for material selection. Polymeric foams as core material in sandwich composites are likely to prevent delamination between face sheets and core by augmenting the contact surface area, resulting from their closed-cell structure. Polymeric foam properties can be enhanced by adding nanomaterials such as carbon nanotubes (CNTs), however increased CNT content or the type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…The test results showed that reinforcements can affect the retardation and/or elimination of core damage, face sheet-core debonding, matrix cracking and fiber breakage in Fiber-Reinforced Composites -Recent Advances, New Perspectives and Applications the sandwich composite structures. With the addition of 0.1 wt.% CNT caused the strengthen of core material, as a result, the ratio of AE signals related to fiber breakage and core damage was decreased[77].Kalteremidou et al used AE to identify the dominant stress/strain component in carbon/epoxy composite materials even before damage mechanisms became evident. The result showed that AE can applied for identification of the dominant stress/ strain component at early loading steps[78].…”
mentioning
confidence: 99%
“…The test results showed that reinforcements can affect the retardation and/or elimination of core damage, face sheet-core debonding, matrix cracking and fiber breakage in Fiber-Reinforced Composites -Recent Advances, New Perspectives and Applications the sandwich composite structures. With the addition of 0.1 wt.% CNT caused the strengthen of core material, as a result, the ratio of AE signals related to fiber breakage and core damage was decreased[77].Kalteremidou et al used AE to identify the dominant stress/strain component in carbon/epoxy composite materials even before damage mechanisms became evident. The result showed that AE can applied for identification of the dominant stress/ strain component at early loading steps[78].…”
mentioning
confidence: 99%